Working in China: Ethnographies of labor and workplace transformation - Ching Kwan Lee (Routledge, 2007)
After a quarter of a century of market reform, China has become the workshop of the world and the leading growth engine of the global economy. Its immense labour force accounts for some twenty-nine per cent of the world's total labour pool but all too little is known about Chinese labour beyond the image of workers toiling under appalling sweatshop conditions for extremely low wages. Working in China introduces the lived experiences of labour in a wide range of occupations and work settings. The chapters of this book cover professional employees such as engineers and lawyers, service workers such as bar hostesses, domestic maids and hotel workers, and industrial workers in a variety of factories. The mosaic of human faces, organizational dynamics and workers' voices presented in the book reflect the complexity of changes and challenges taking place in the Chinese workplace today. Based on extraordinary and thorough field research, this book will have a wide readership at undergraduate level and beyond, appealing to students and scholars from a myriad of disciplines including Chinese studies, labour studies, sociology and political economy.
Keywords: 330